The Effect of Academic Hardiness and Grit on Students Academic Stress in The Online Learning Process During Pandemic COVID-19 - Yulia Hairina; Rika Vira Zwagery; Imadduddin Imadduddin; Muhammad Arsyad (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: This study was conducted to find out the significance of academic hardiness and grit on students academic stress students who have experienced the online learning process during the Covid-19 pandemic. The research method used is quantitative research methods.  The number of samples in this study was 200 respondents who were selected using nonprobability sampling. Instruments used in this study there are three scales, they are Short Grit Scale (Grit-S) to measure Grit, Academic Hardiness Scale RAHS to measure academic hardiness and Perceived Stress Inventory for Academic Stress (PSI) to measure academic stress. While the data analysis using multiple regression techniques. The results of this study indicate that there is a significant influence of academic hardiness and grit on students academic stress. The amount of influence of all independent variables on grit is 29.4%, while the rest is influenced by other variables outside this research. So the students who have experienced online learning during the Covid-19 pandemic and began to experience stress because of this can try to apply hardiness and grit. In addition, they need also to have faith in their academic ability during online learning so they can have more positive though and not being vulnerable to stress.